Understanding the Impact of the Cultural Factors on Hospital Information System Acceptance: A Literature Review and Proposal of a New Model - Benali Idrissi Ouiame; Chafik Khalid; Boubker Omar (European Scientific Journal, ESJ, 2018)
The behavioural intention to accept information system technologies remains an interesting research field for information system management specialists and researchers. However, the cultural dimension has rarely been treated by researchers in the healthcare context. This paper focuses on identifying the impact of national culture on users’ intention to accept the Hospital Information System in public healthcare establishments in Morocco. Thus, we propose a research model which is based on a strong literature review, taking into consideration the previous studies’ recommendations and limitations. The proposed model was developed through the extension of the Technology Acceptance Model (TAM) (Davis, 1989), by Hofstede’s cultural dimensions.